Perceptions and Prevention of Unwanted Pregnancy among the Akha Adolescents - Chansiri, Suphaphan; Wongwatkit, Charoenchai (Nursing Science Journal of Thailand, 2022)
Purpose: To explore the perceptions of unwanted pregnancy and the prevention of unwanted pregnancy among the Akha adolescents in Chiang Rai Province. Design: Exploratory qualitative research design. Methods: The study included 42 Akha adolescents in Chiang Rai Province. Data were collected through in-depth interview using a semi-structured questionnaire. Information gathered from the participants were analyzed by using descriptive statistics and content analysis approach. Main findings: Five themes arose from data analysis, which are: 1) Unwanted pregnancy is the problem of themselves, families, and society. 2) Knowledge about unwanted pregnancy and the prevention are learned from schools, families, communities, and healthcare providers. 3) Prevention of unwanted pregnancy is challenging. 4) Factors affecting the unwanted pregnancy. 5) A need for increasing knowledge and receiving health service for preventing unwanted pregnancy. These perceptions have a great impact on preventive behaviors of unwanted pregnancy among Akha adolescents. Conclusion and recommendations: The Akha adolescents have a perspective toward unwanted pregnancy in a negative way. The prevention of unwanted pregnancy is challenging due to several factors affecting the risky sexual behaviors. Most participants gain knowledge about unwanted pregnancy and the prevention from school; nonetheless, insufficient information from communities and health care providers is obtained. The study suggests that the healthcare providers should actively involve in providing knowledge in schools and communities, as well as developing online learning applications for Akha adolescents, with the concern of Akha’s context and culture.